Perempuan Berpolitik dalam Perspektif Islam - Rusnila Rusnila (Raheema, 2014)
“Woman” undoubtedly becomes the most talked issue. The debate of this matter is not only about the sex differences but also about the existent role in the society. Furthermore, woman will be more striven when her existence being asked in publicly. Traditional thought considers the existence of woman by limiting the civilization. On the other hand, open minded and modernization trait lead the woman existence by describing her potential traits. As a part of life, politics is an entrance for women to develop their willingness to be more recognized in the society. Besides, there are theological issues which merge in the process of women recognizing in a political field.